Water column stability and summer phytoplankton dynamics in a temperate lake (Lake Erken, Sweden). Issue 4 (1st January 2016) - Yang, Yang; Colom, William; Pierson, Don; Pettersson, Kurt
Abstract: Phytoplankton development in aquatic ecosystems is caused by interactions among multiple environmental factors. Physical processes, particularly development of thermal stratification, have been proposed to be important factors for regulating phytoplankton composition and abundance during summer. This study examined the temporal pattern of thermal stratification during summer in Lake Erken, Sweden, based on 21 years of historical data spanning 23 years and investigated the role played by water stability on phytoplankton development. Water column stability indexes were calculated from high frequency measurements during periods of summer thermal stratification. Clustering and ordination analyzed the dissimilarities between communities during different periods and extracted the significant environmental gradients controlling phytoplankton succession. Wind introduced the major external disturbance to Lake Erken during summer and played an important role for the progression of thermocline depth. Species-specific thermal stability preference or tolerance determined the response of individual species to the stratification and constitutes a mechanism of species selection in phytoplankton dynamics. Lake Erken is an unstably stratified lake during summer, caused by wind-induced turbulence and internal seiches. Adaptation to these unstable conditions is the major determinant of phytoplankton dynamics. Hydrodynamic variability, characterized by different stability indexes in early, mid, and late summer, was the key factor regulating phytoplankton dynamics, directly by changing phytoplankton distribution and indirectly by altering both the light and nutrient availability in the epilimnion.